Automated system for the researching of IP-connections quality - Олійник, Андрій Олександрович; Головко, Максим Володимирович; Федорченко, Євген Миколайович (Eastern-European Journal of Enterprise Technologies, 2013)
The work is devoted to the issues of the researching of ip-connections quality. Recently, IP-technology becomes widely spread at the market of communication services. Role of communication quality influences the performance of corporate information systems and services. Due to the great diversity of packet services, families of protocol stacks of packet commutation and implementation methods in the equipment of different manufacturers it becomes difficult to create the normative basis in the field of metrology IP services and certification of measuring equipment. The aim is to create a hardware-software system for managing SLA (Service Assurance Agent). Designed multifunctional hardware and software system for managing SLA which has the large functionality of expensive measurement equipment, and due to the software application it has a huge advantage, lower price. Required measurements properties are realized thanks to the use of a hardware platform that provides the necessary monitoring services SLA accuracy and reliability of measurements. The usage of probes software components allows to quickly change the functionality of the probes on demand without changing hardware platforms, providing the reasonable rate of changes. Measuring mechanisms are based on current guidelines and standards in the field of metrology and qualimetry